2022
DOI: 10.3390/healthcare10091772
|View full text |Cite
|
Sign up to set email alerts
|

Association between Vitamin D and Cognitive Deficiency in Alcohol Dependence

Abstract: There are still not enough findings to elucidate how exactly alcohol use impairs cognitive abilities. Some studies have shown that there is a link between alcohol intake and vitamin D levels, but these findings are inconsistent so further research is needed. The aim of this study was to investigate the association between serum vitamin D levels and cognitive impairment in alcohol-dependent individuals. A case-control study was carried out including a total of N = 132 respondents with a medical history of alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
(68 reference statements)
0
0
1
Order By: Relevance
“…In this study, the prevalence of vitamin D deficiency was greater than the prevalence found in other series of treatment-seeking patients with AUD, as studies from Asia and Northern and Central Europe reported a prevalence ranging from 60% and 75% [ 18 , 19 , 20 , 21 , 22 ]. A recent Spanish study among patients with severe AUD admitted to an internal medicine ward in the Canary Islands reported a prevalence of vitamin D deficiency of 28% [ 23 ].…”
Section: Discussioncontrasting
confidence: 48%
“…In this study, the prevalence of vitamin D deficiency was greater than the prevalence found in other series of treatment-seeking patients with AUD, as studies from Asia and Northern and Central Europe reported a prevalence ranging from 60% and 75% [ 18 , 19 , 20 , 21 , 22 ]. A recent Spanish study among patients with severe AUD admitted to an internal medicine ward in the Canary Islands reported a prevalence of vitamin D deficiency of 28% [ 23 ].…”
Section: Discussioncontrasting
confidence: 48%